ERRORS MADE BY THE PRESENTERS OF THESIS PROPOSAL SEMINAR IN STUDY PROGRAM OF ENGLISH UNIVERSITAS BRAWIJAYA - AZIZ, JALAL ABDUL (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Error, Error Analysis, thesis proposal seminar, Communicative EffectTaxonomy, global errors, local errors, eighth semester students.One of the most important languages to learn today is English since it is widely spoken around the world. In learning another language including English, a learner sometimes produces errors and Error Analysis (EA) has a methodology to figure them out. One of the methodologies is Communicative Effect Taxonomy. In this study, the writer analyzed errors made by the presenters of thesis proposal seminar in Study Program of English Universitas Brawijaya based on Communicative Effect Taxonomy. Furthermore, the writer proposed two objectives of the study, (1) To find out the types of errors made by the presenters of thesis proposal seminar based on Communicative Effect Taxonomy; (2) To find out whether or not global errors of Communicative Effect Taxonomy made by the presenters of thesis proposal seminar significantly hinder communication between the presenters and the audiences.This study used qualitative approach because the data of this study was taken from 4 students’ presentations which were in the form of words rather than number and statistic. The researcher analyzed the data by using the theory of Communicative Effect Taxonomy.This study revealed that there were 188 errors committed by the students in which 179 and 9 erroneous utterances fall under local error and global error respectively. The local errors consist of 45 lexical errors, 93 morphological errors, and 41 syntactical errors. The global errors consist of 2 wrong order of major constituents, 1 missing, wrong, or misplaced sentence connectors, 1 missing, wrong, or misplaced sentence connectors, and 5 uncategorized global errors. As for the effect of global error to the audience, the writer found out that the global errors did not significantly hinder communication to the audience.The writer suggests the next researchers who want to conduct similar research to use another subject or another theory. Another suggestion is to use the similar theory but with different object.